Maternal Diet During Pregnancy and COVID-19 Susceptibility of Offspring: The â€œThrifty Phenotype Hypothesisâ€ Connection - Deocaris, Custer C; Alinsug, Malona V (Journal of Tropical Life Science, 2021)
There is accumulating evidence suggesting that ACE2, the host cell receptor for the spike (S) protein of the SARS-CoV-2, mediates viral entry and infection, is under epigenetic control. Here, we discuss studies suggesting a nutritional strategy for down-regulating ACE2 expression in tissues of offspring through the phenomenon of maternal epigenomic reprogramming mediated by maternal diet. The